Clinical efficacy of sublingual immunotherapy for house dust mite-allergic rhinitis with sleep disturbances - Ikeda, Katsuhisa; Ide, Takuma; Inoshita, Ayako; Nakamura, Masahiro; Matsumoto, Fumihiko (Journal of Immunology, Allergy and Infection in Otorhinolaryngology, 2022)
Allergic rhinitis (AR) causes sleep disturbances. However, studies reporting the impact of sublingual immunotherapy (SLIT) for AR-related sleep disturbances are limited. The purpose of this study was, for the first time, to evaluate in detail the impact of a 6-month SLIT treatment on the quality of sleep in house dust mite (HDM)-AR patients.The total nasal symptom score (TNSS) and sleep disturbances in AR patients sensitive to HDM (n=23) were evaluated and compared using questionnaires accomplished by those who participated in the study. The questionnaire-based evaluation was repeated after 6 months of SLIT treatment to investigate the changes in TNSS and sleep disturbances due to the therapeutic intervention. We classified the subjects into two groups based on the baseline Pittsburgh sleep quality index (PSQI) score: one with no sleep disturbances before the start of treatment (normal-sleeping subjects, n=10, PSQI<6) and the other with sleep disturbances (poor-sleeping subjects, n=13, PSQI≥6).PSQI was correlated positively with nasal obstruction score in the pretreatment phase (r=0.66, p<0.05). TNSS and PSQI scores improved significantly after 6 months of SLIT. After stratification, the nasal obstruction scores and PSQI scores did not vary significantly before and after treatment in the normal-sleeping subjects’ group, but the other group showed significant improvements after treatment.SLIT may improve both nasal symptoms and the quality of sleep in HDM-AR patients suffering from sleep disturbances. Therefore, encouraging patients with AR to continue SLIT for as long as possible may help in improving their sleep quality.